PENGGUNAAN METODE RAPID VISUAL SCREENING DALAM MENENTUKAN KERENTANAN BANGUNAN AKIBAT GEMPA BUMI - Indra Birawaputra; Yoga C. V. Tethool (INTAN Jurnal Penelitian Tambang, 2019)
Sorong is a city located at the junction of three tectonic plates. Thus, makes the city vulnerable to earthquake hazards. Evaluation on building vulnerability is needed to determine the damage mitigation due to an earthquake. As a populous area, Moyo residential area requires building vulnerability evaluation of earthquake hazard. Rapid Visual Screening according to FEMA P-154 2015 is used to evaluate the building vulnerability. This method requires input data such as seismic location, building occupancy, soil type, building typology, number of story, vertical irregularities, plan irregularities and code. The analysis result showed that the level of vulnerability for building typologies W1, RM1 and C3 were 0.09%, 1.01% and 32.62%.